The difference of tensile bond strength between total and self etch adhesive systems in dentin - Selly Yusalina; Moch. Richata Fadil; Milly Armilia (Padjadjaran Journal of Dentistry, 2010)
Total etch adhesive system has been widely used in teeth conservation area as an adhesive agent before implicating composite resin restoration agent. The aim of this research is to prove the difference of tensile bond strength between total etch (Single Bond) and self etch adhesive system (Adper prompt L-Pop) on dentin surface in vitro. The extracted and non carries maxillary premolar teeth were used in this research and were divided into 2 groups. The first group comprised 15 specimen teeth etched in phosphoric acid and was applicated with the Single Bond adhesive agent. The second group comprised 15 specimen teeth, applicated with the Adper Prompt-L-Pop. The composite resin (Z 350, 3M) was applied incrementally and each of the layers was rayed for 20 seconds. The specimens were stored in physiologic solution before they were tested. Tensile bond strength was measured by LRX Plus Lloyd Instrument, with 1 N load and 1 mm/minute speed, and the measurement result was in Mpa unit. The result was evaluated statistically by the Student t-test with α = 0.05. Single Bond (the 5th generation) showed a better bond strength compared to the Adper Prompt-L-Pop (the 6th generation).